(untitled) - Morgan, Victor (New York,Cambridge [England], 2004)
This volume brings to completion the four-volume series, a vital contribution to academic history. Special features of this volume relate it to social and political history--especially to the gentry who provided patronage and recruits, as well as the royal court and parliament. The history of the university features extensive material on its architectural heritage, and a chapter on such intellectual giants between 1660-1740 as Richard Bentley and Isaac Newton.
Keywords: University of Cambridge,History,Trường Đại học Cambridge,Lịch sử